Simplified control strategy of shunt active power filter based on nonlinear load equivalent active impedance estimation / Yushaizad Yusof - Yushaizad, Yusof (2019)
This thesis proposes a new simplified control strategy for the single phase shunt active power filter (SAPF) system. The SAPF circuit injects a compensated current comprising harmonics and reactive current components of load current but with opposite phase at the point of common coupling (PCC) of the line so that the source current will be free from harmonic distortion as well as in phase with the source voltage. By using a nonlinear load equivalent resistance estimation control strategy, the source voltage should see a load as a near pure resistor. The proposed control strategy features simple configuration and has only two mathematical division operations. Therefore, the nonlinear load equivalent resistance can be determined by dividing an average DC load voltage over an average DC load current. Both quantities are obtained from filtered absolute values of source voltage and load current respectively. A sinusoidal reference current is obtained by dividing the source voltage over the calculated equivalent resistance. The feedforward load current subtracted the sinusoidal reference current to yield a compensated reference current. Next, the actual compensated current need to be feedback and subtracted by the reference compensated current at set point to produce an error signal. In order to compensate the error signal, a proportional (P) and proportional plus integral (PI) controllers are employed to yield a control signal. Then, the control signal is compared with a 20 kHz carrier signal to form pulse width modulation (PWM) gating signals that drive Insulated Gate Bipolar Transistor (IGBT) switches of full bridge voltage source inverter (VSI) based SAPF configuration. Computer simulation and experimental work were carried out for verification purpose. As a result, the total harmonics distortion (THD) of source current after compensation has been attenuated significantly below IEEE Std. 519 and IEC61000-3-2 standards respectively. Besides, the line’s power factor also remarkably improved to near unity (0.999). Moreover, the SAPF demonstrated a good and fast dynamic response capability under a sudden change in load and source as well as instantaneous connection and disconnection with the line. Furthermore, the developed analog controller circuit is inexpensive and offers easy implementation. On top of that, the proposed Trapezoidal rule based low pass filter has better performance than conventional Butterworth and first order RC low pass filters (LPF) in term of dynamic response and output ripple content.